Homebuyers Beware: Whos Ripping You Off Now?--What You Must Know About the New Rules of Mortgage and Credit - Warren, Carolyn (Pearson Education, 2012)
This book reveals new secrets homebuyers simply can’t afford to miss and exposes new scams that target today’s eager consumers--including new loans that look great on paper but are every bit as dangerous as yesterday’s subprimes.